Short light/dark cycles favour photosynthetic efficiency and growth in grapevines - Mariana Gómez Tournier; Laurent Torregrosa; Jana Kändler; Angélique Christophe; Romain Boulord; Anna Medici; Anne Pellegrino (OENO One)
Climate change and the expansion of the urban frontier pose a threat to the sustainability of agricultural systems. In this context, confined cultivation systems can provide a viable alternative for maintaining consistent production levels. Light and temperature in greenhouses or growth chambers are major regulatory factors in plant functioning, which can be easily modulated. Shortening the photo-/nycti-periods, compared to the standard cycle (12 h light/12 h dark), has been shown to enhance the photosynthetic activity and growth in annual crops, but its effect on perennial crops such as grapevines remains unexplored. This study aimed to describe the effects of accelerating the light/dark cycle to a repeated short pattern (3 h light/3 h dark, ‘T3/3’), in contrast to the circadian-aligned regime (12 h light/12 h dark, ‘T12/12’) while keeping the same temperature and photosynthetic active radiation amounts per day. We evaluated photosynthetic efficiency, leaf growth, biomass production and partitioning, and resource use efficiency (water and light).